Residual Properties of Fiber Reinforced Concrete (FRC) - Abdul Rahman, Muhammad Fuad; Ayop, Sallehuddin Shah; Muhammad Azim Ab Rahaman (Recent Trends in Civil Engineering and Built Environment, 2025)
Fibre-reinforced concrete (FRC) is a composite material that incorporates discrete fibres into the concrete mixture to improve its mechanical properties. The fibres used in FRC can be made of materials such as steel, glass, synthetic fibres, or natural fibres. The characteristics or behaviours of a material that persist after being exposed to a processor environment are known as residual properties. This study will use an experiment to examine the characteristics of concrete using various shapes, mainly cubes and prisms. Compressive and flexural tests are the two main tests that will be used in this experiment. The primary material that will be used as a crucial component in this experiment is polypropylene fibre. The residual of fibre concrete will be evaluated by different percentages of fibre content, which are 1%, 1.5%, and 2%. The test evaluation will be done after the concrete reaches age of 28 days. The total sample for this experiment is 24. According to the findings of this study, fibre reduces the workability of a concrete mix. The increase in polypropylene fibres in the concrete reduces the workability value of the concrete. In a similar manner, the presence of fibres in the concrete reduces compressive strength. However, the compressive strength remained within the experimentally specified range. In fact, this study examined flexural tests, and it was discovered that high load values were obtained from concrete with a high fibre percentage of 2%. In addition, the research was also conducted in terms of peak strength, peak load deflection, and residual value, with a high fibre percentage dominating the highest value in the study. The residual value for this study was discovered to occur only at a deflection of 2 mm. Finally, the percentage of flexural strength was found to be increasing in parallel with the percentage of fibres in concrete.